SAT0035 Impact of Corticosteroid Use on Remission Sustainability and Infection Rates among Rheumatoid Arthritis Patients in Remission While on Infliximab: Treatment Implications Based on A Real-World Population. (10th June 2014) - Haraoui, B.; Jovaisas, A.; Bensen, W.; Faraawi, R.; Kelsall, J.; Dixit, S.; Rodrigues, J.; Sheriff, M.; Rampakakis, E.; Sampalis, J.S.; Lehman, A.; Otawa, S.; et al.
Abstract : Background: According to current treatment guidelines short-term treatment with corticosteroids (CS) can be considered in rheumatoid arthritis (RA) patients treated with a traditional and/or biologic DMARD, and should be tapered as rapidly as clinically feasible 1, 2 . Objectives: The aim of the current analysis was to examine the use of systemic CS among patients in remission, to evaluate their usefulness in sustaining disease remission, and assess their impact on the incidence of infections in RA patients treated with infliximab in a real-world, routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with IFX or golimumab as first biologics or after having been treated with a biologic for <6 months. For the purpose of this study only RA patients treated with infliximab between 2002 and 2012 were included. Cox regression was used to examine the time-dependent association between systemic CS use (yes vs. no) and sustainability of remission or incidence of a subsequent infection. Results: Six-hundred twenty-eight RA patients were included in the analyses. Mean (SD) age was 55.8 (13.6) years and mean (SD) duration since diagnosis was 10.2 (10.0) years. Remission as defined by the DAS28 and CDAI was achieved by 46.5% and 30.4% of patients, respectively. Despite the achievement of remission, CS use was continued in 16.4% and 16.7% of cases, respectively. In these patients, survival analysis did not show a significant positive effect of CS use on sustainability of remission [HRDAS28 (95%CI) =1.40 (0.95-2.06); HRCDAI (95%CI) =1.19 (0.75-1.88)]. Conversely, time to acquiring an infection was significantly shorter among patients treated with a CS when compared to the absence of CS treatment [HRCDAI (95%CI) =2.38 (1.14-4.99)]. Conclusions: The results of this real-world observational study have shown that, despite the achievement of remission, CS use was continued in approximately 16% of cases. Treatment with CS was associated with an increased risk for acquiring an infection without having an impact on sustainability of remission. The results of this analysis support the recommendation that CS should be used concomitantly with anti-TNF treatment for the shortest period possible to achieve remission but not thereafter. References: Bykerk VP et al. J Rheumatol 2012;39;1559-1582 Smolen JS et al. Ann Rheum Dis. 2013; Epub ahead of print Disclosure of Interest: B. Haraoui: None declared, A. Jovaisas: None declared, W. Bensen: None declared, R. Faraawi: None declared, J. Kelsall: None declared, S. Dixit: None declared, J. Rodrigues: None declared, M. Sheriff: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, A. Lehman Employee of: Janssen, S. Otawa Employee of: Janssen, F. Nantel Employee of: Janssen, M. Shawi Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.2386